PROPUESTA DE UN MANUAL DE POLÍTICAS CONTABLES BAJO LA APLICACIÓN DE LAS NORMAS INTERNACIONALES DE INFORMACIÓN FINANCIERA PARA LA COOPERATIVA DE TRANSPORTES LOJA, PERIODO 2017 - Paz Cuenca, Carolina Michelle (2018)
The present document denominate "PROPOSAL OF A MANUAL OF ACCOUNTING POLICIES UNDER THE APPLICATION OF INTERNATIONAL FINANCIAL REPORTING STANDARDS FOR THE COOPERATIVE TRANSPORT LOJA, Period 2017", was developed in compliance with the objectives set. The first objective is to determine the main accounts of greater movement that the Cooperative, which present shortcomings in their records and whose recognition is required by IFRSS, which was conducted through the application of an analysis of the accounts that presented a higher relative importance in the financial statements, the second objective is to determine the main International Financial Reporting Standards and regulations governing transport cooperative to Loja, in order to channel and set the governing the entity object of study, which included a synthesis and comparison between the specific rules governing the entity with the rules of the international standard; the third Objective: to establish accounting policies for the main groups of accounts that present shortcomings, together with the application of the IFRS's in force at the time; that was carried out through the recognition, measurement, policy approach and the information to be disclosed for the interpretation of financial information in relation to the selected accounts and diagnosed in the first goal; and the fourth objective which is to hand over to the main authorities of the Cooperative Transport 5 Loja the proposal of the Manual of Accounting Policies under IFRS's, for which it submitted a copy of the present work and recorded through a document signed by the highest authority of the entity. At the end of the proposal of the manual of accounting policies it is concluded that, constitutes a tool for information about the database and accounting policies essential for the preparation and presentation of financial information, so that their use is recommended to improve the processes, and mechanisms in the registration and preparation of the financial statements to enable managers to know the reality of the financial and economic situation for the taking of decisions.